Characterization of melanoidins formed from glucose and some α- carbonyl compounds with alanine by NMR spectroscopy - Mohsin, Ghassan Faisal (Journal of natural sciences, life and applied sciences, 2019)
In this study, NMR spectroscopy can be used to investigate and quantify selected chemical bonds in different melanoidins formed from glucose and some Maillard intermediates as HMF, MGO and GO with alanine. Chemical shifts between 100 ppm and 160 ppm are characteristic for sp2 hybridized carbons as found in conjugated double bond systems (C=C). The sp2 hybridized carbons cannot be found in melanoidin formed from Glc/Ala in the region between 110 ppm and 160 ppm and showing a higher content of sp2 hybridized carbon than in HMF/Ala, GO/Ala and MGO/Ala. Melanoidins formed from HMF/Ala, GO/Ala and MGO/Ala have been shown to be HMW compounds and LMW in melanoidin from Glc/Ala using UV/Vis, FTIR and NMR spectroscopy.